Fundamentals of Artificial Stimulation in the Retina: From Neuronal Activation to Bioelectronic Interfaces - Raghuram, Vineeth. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Brian Timko.; Committee: Shelley Fried, Xiaocheng Jiang, and Barry Trimmer.; Keyword: Biomedical engineering.